The Impact of Educational Motivation and Self-acceptance on Creativity among High School Students. Issue 4 (1st October 2020) - Mostafavi, Hossein; Yoosefee, Sadegh; Seyyedi, Seyyed Ali; Rahimi, Maryam; Heidari, Morteza
ABSTRACT: Education and creativity are interrelated, and motivation is regarded as a factor influencing creativity. On the other hand, it seems to be a connection between creative achievements and one's perceptions about oneself including self-acceptance. The aim of this study was to investigate the impact of educational motivation and self-acceptance on creativity among high school students. Three hundred and sixty-one high school students in Saveh city, central Iran, participated in this correlational study. The participants filled out the Ryff Scale of Psychological Well-being (RSPWB-18), Abedi Creativity Questionnaire, and Harter's Classroom Affect and Motivational Scale. The findings indicated a significant relationship between students' educational motivation and their creativity ( P <.01), but no significant relationship between self-acceptance and creativity. According to the results of this study, creativity of students increases along with their educational motivation.